PENGARUH PELAKSANAAN PENGAWASAN MANDOR TERHADAP KINERJA KARYAWAN ( KASUS BAGIAN PRODUKSI PADA PT. GELIGA BAGAN RIAU - ROKAN HILIR ) - Prayoga, Septian Adi; ", Ruzikna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study aims to determine the effect of the implementation of the foreman monitoring the performance of employees at PT. Geliga Chart Riau. Rokan downstream. Supervision foreman as the independent variable (X). While employee performance as the dependent variable (Y). This study was conducted on all employees of PT. Geliga Chart Riau. Rokan downstream as many as 54 people. Data obtained from questionnaires and subsequently processed to then be tested using statistical analysis as a simple linear regression analysis, t test, and correlation analysis and determination using SPSS. The results showed that the results of the t test of hypothesis testing. T count> t table (8.072> 2.080) and Significance <0.05 (0.000 <0.05). This suggests that the effect of the implementation of supervision foreman influence on employee performance. The magnitude of the effect of the implementation of the surveillance supervisor to employee performance at PT.Geliga Chart Riau. Downstream rokan 55.6. Keywords: Human Resources, Monitoring, Performance.